From phosphaphenalenes to diphosphahexaarenes: an overview of linearly fused six-membered phosphorus heterocycles - Regulska, Elzbieta; Hindenberg, Philip; Romero-Nieto, Carlos (European journal of inorganic chemistry, 2019)
The chemistry of linearly fused systems based on six-membered phosphorus heterocycles is currently experiencing an astonishing evolution. Even though the phosphorus analogs of naphthalene and anthracene were first synthesized in the late 1960s, laterally fused phosphorus heterocycles have recently demonstrated outstanding performances as biomarkers, sensors, and luminescent systems for organic electronics. In this microreview, we provide a comprehensive revision of relevant linearly fused systems based on six-membered phosphorus heterocycles from their origin to the latest advances on the largest derivatives.
First published: 17 January 2019
Gesehen am 21.05.2019